Revisiting the Sustainability of Kerala State Finances - Liji Lakshmanan, T. (Arthshastra Indian Journal of Economics & Research, 2019)
Using yearly data from 1970-71 to 2015-16, the paper tried to find out whether fiscal sustainability existed in Kerala or not. It also examined whether structural breaks are present in the fiscal policy. Applying cointegration techniques with breaks and no breaks to the inter-temporal budget constraint model, the paper concluded that sustainability of current fiscal policy of Kerala was weak, which implies a long-run risk of debt default in Kerala State finances.